2020
DOI: 10.1002/anie.202008356
|View full text |Cite
|
Sign up to set email alerts
|

Making or Breaking Metal‐Dependent Catalytic Activity: The Role of Stammers in Designed Three‐Stranded Coiled Coils

Abstract: While many life-critical reactions would be infeasibly slow without metal cofactors, a detailed understanding of how protein structure can influence catalytic activity remains elusive. Using de novo designed three-stranded coiled coils (TRI and Grand peptides formed using a heptad repeat approach), we examine how the insertion of a three residue discontinuity, known as a stammer insert, directly adjacent to a (His) 3 metal binding site alters catalytic activity. The stammer, which locally alters the twist of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…This peptide is structurally analogous to the two a -site Cys layers in ORF1p­CCD (Figure A). We note that this model lacks the three-residue stammer insertion discontinuity, which we recently suggested influences proximal metal binding sites . Lead titrations to GRCS ­L16CL23C show the characteristic 343 nm peak, again indicative of PbS 3 formation within the 3SCC interior.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…This peptide is structurally analogous to the two a -site Cys layers in ORF1p­CCD (Figure A). We note that this model lacks the three-residue stammer insertion discontinuity, which we recently suggested influences proximal metal binding sites . Lead titrations to GRCS ­L16CL23C show the characteristic 343 nm peak, again indicative of PbS 3 formation within the 3SCC interior.…”
Section: Resultsmentioning
confidence: 52%
“…38 Additionally, we have shown that adding a stammer discontinuity to a 3SCC alters the reactivity of both Zn and Cu designed enzymesin one case diminishing and in the other enhancing activitysuggesting that metal-based function can be modulated by sequence discontinuities in 3SCCs. 22 Taken together, this evidence demonstrates the possibility of Pb(II) interference to the human LINE-1 ORF1pCCD. The formation of the trigonal pyramidal Pb(II)S 3 complexes in the interior tristhiolate sites of the trimer could alter coiled-coil stability and dynamics, which are factors that have been shown to be critical in retrotransposition of L1.…”
Section: ■ Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Chiral metal-coordinated supramolecular assemblies have recently received much attention and are among the most promising structures in supramolecular chemistry, [1][2][3][4][5][6][7][8][9][10] because metal-coordinated systems play essential roles in the formation of superstructures such as coiled-coil helix bundle proteins, 11,12 DNA superhelices, 13 and protein-DNA hybrid superstructures. 14,15 Thus, better understanding of emergent chiral phenomena and the origin of chirality at the supramolecular level are essential for biomedical applications such as drug delivery, [16][17][18] gene delivery, 19 tissue engineering, 20,21 imaging, 22 and sensing.…”
Section: Introductionmentioning
confidence: 99%